Selenium-enriched Cardamine violifolia improves growth performance with potential regulation of intestinal health and antioxidant function in weaned pigs - Wang, Dan; Zhang, Yue; Chen, Qinliang; Kuang, Yanling; Fan, Jiajun; Xu, Xiao; Zhu, Huiling; Gao, Qingyu; Cheng, Shuiyuan; Cong, Xin; Liu, Yulan (Frontiers in Veterinary Science, 2022)
This study was conducted to evaluate the effects of different Selenium (Se) sources on growth performance, intestinal function and antioxidant status of weaned piglets. A total of 300 weaned pigs were randomly allocated to 5 treatment groups with 5 replicates of 12 pigs/pen. The control group was corn-soybean basal diet without any additional Se supplement. The experimental diets were supplemented with 0.3 mg/kg of Se from sodium selenite (SS), Se-enriched yeast (SEY), Se-enriched Cardamine violifolia (SEC) and 0.3+0.3 mg/kg of Se from SEY and SEC, respectively. The trial lasted for 4 weeks. The results showed that diets supplementation with SEY, SEC or SEY+SEC could improve average daily gain and reduce feed/gain ratio during the entire study. Compared with the control group, SEC or SEY+SEC improved intestinal morphology, indicated by greater villus height and villus height/ crypt depth ratio. In addition, SEC or SEY+SEC also increased maltase and lactase activities as well as tight junction protein expression. Different Se sources decreased malondialdehyde (MDA) concentration and improved superoxide dismutase (SOD) activity in serum. In the jejunum, SEY or SEC reduced MDA concentration and increased total antioxidant capacity (T-AOC) compared with the control group. Moreover, SEY+SEC increased the antioxidant parameters including SOD and T-AOC in the jejunum. Dietary SEY or SEC supplementation significantly increased the mRNA expression of selenoproteins including thioredoxin reductase 1 (TXNRD1), selenoprotein I (SELENOI), selenoprotein S (SELENOS) and selenoprotein P (SELENOP) in the jejunum. In conclusion, organic Se sources, especially Cardamine violifolia, improve growth performance, potentially by regulating intestinal function, antioxidant capacity and selenoprotein expression in piglets.